Pancreas volume and fat deposition in type II diabetes mellitus - Ramanaidu, Anusha A/P (2022)
Diabetes mellitus is a metabolic disease associated with a defect of β cell function that causes insulin resistance characterised by hyperglycemia. In the diabetes mellitus population, the reduction of pancreatic volume and an increase in the pancreas attenuation cause uncontrolled sugar in patients. In patients with type II diabetes mellitus, there is a strong association between pancreas volume and pancreatic attenuation. Many studies conducted in Europe and other Asian countries showed diabetes mellitus has an association with reduced pancreas volume and an increase in pancreas attenuation in diabetes mellitus population. The aim of this study is to establish a significant reduction in pancreatic volume and an increase in the pancreatic attenuation in type II diabetes mellitus, in comparison with the non-diabetes mellitus population, based on the assessment using computed tomography (CT) among the Malaysian population. In Malaysia, no study has been conducted to evaluate pancreas changes among type II diabetes mellitus patients. The various external factors such as lifestyle, diet, and body habitus influence these pancreatic changes. Another objective is to see metabolic factors’ association with type II diabetes mellitus patients.